2012
DOI: 10.1002/polb.23220
|View full text |Cite
|
Sign up to set email alerts
|

Hydration studies in polymer hydrogels

Abstract: Polymer hydrogels have attracted much interest in recent years based on numerous applications mainly in biotechnology and medicine. For the knowledge-based design and development of new materials for these and similar applications, it is essential to understand better the hydration properties of hydrogels and of polymers in general. With this term, we mean the particular organization of water in the hydrogel, which determines the properties of the water component, typically different than those of bulk water, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 131 publications
4
66
0
Order By: Relevance
“…In addition, dielectric measurements were performed at various levels of water content, providing information about effects of water on polymer dynamics, which can be correlated with water uptake. 44 …”
mentioning
confidence: 97%
“…In addition, dielectric measurements were performed at various levels of water content, providing information about effects of water on polymer dynamics, which can be correlated with water uptake. 44 …”
mentioning
confidence: 97%
“…In addition, correlations were observed between results on the organization of water in the hydrogels and on water effects on polymer dynamics. In particular, distinct changes in the dielectric response at the water content of the completion of the first hydration layer indicated that water molecules themselves contribute to the dielectric response at higher water contents [20]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Despite the extended use of HA hydrogels in biological applications, the dielectric behavior of such materials at low water concentrations and subzero temperatures has not been studied so far in detail.…”
Section: ) Introductionmentioning
confidence: 99%
“…In the case of globular proteins the observed dielectric relaxation associated to the calorimetric glass transition has been attributed in literature to a combined motion of uncrystallized water molecules in the protein hydration shell and segments of the protein surface [19,24,25,30]. Measurements in synthetic hydrogels based on poly(hydroxyl ethyl acrylate) (PHEA) by dielectric and other experimental techniques showed that the segmental α relaxation (dynamic glass transition) is significantly plasticized by water [20]. In addition, correlations were observed between results on the organization of water in the hydrogels and on water effects on polymer dynamics.…”
mentioning
confidence: 99%
See 2 more Smart Citations